2015
DOI: 10.7342/ismt.rpics.2015.1.2.23
|View full text |Cite
|
Sign up to set email alerts
|

Validação da versão portuguesa da Center for Epidemiologic Studies Depression Scale for Children (CES-DC)

Abstract: Objetivo: A depressão na infância e na adolescência, tal como na população adulta, é uma das perturbações mentais mais comuns. Uma vez que o seu aparecimento nestas faixas etárias se associa a consequências graves na idade adulta, é fundamental identificar os sintomas depressivos precocemente. Desta forma, os instrumentos de autorrelato têm um papel fundamental, uma vez que permitem com facilidade, de forma fidedigna e válida, ter acesso a formas de pensar, sentir e agir dos sujeitos. O objetivo do pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Specifically, gender differences in the severity of depressive symptoms only appeared for older adolescents (above 14.62 years), with girls presenting higher levels than boys. Although other studies have also shown no gender [ 19 , 50 ] and age-related [ 19 , 50 , 63 ] differences, most studies have revealed an increase in depressive symptoms throughout adolescence and gender differences starting in the earlier years of adolescence [ 1 , 64 , 65 ]. Possibly, the short age range of our sample may have limited our ability to capture an onward increase in depressive symptoms over adolescence and the gradual emergence of gender differences, until these became more expressive in the older adolescents of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, gender differences in the severity of depressive symptoms only appeared for older adolescents (above 14.62 years), with girls presenting higher levels than boys. Although other studies have also shown no gender [ 19 , 50 ] and age-related [ 19 , 50 , 63 ] differences, most studies have revealed an increase in depressive symptoms throughout adolescence and gender differences starting in the earlier years of adolescence [ 1 , 64 , 65 ]. Possibly, the short age range of our sample may have limited our ability to capture an onward increase in depressive symptoms over adolescence and the gradual emergence of gender differences, until these became more expressive in the older adolescents of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…We used the CES-D questionnaire instead of the Beck questionnaire before enrollment of participants because the CES-D was already validated for use in the Portuguese language. 12 Moreover, depressive symptoms were listed primary outcome in the revised version correcting a previous mistake that listed this variable as a secondary outcome. All parents were informed of the research through the Informed Consent Term and the adolescents through the Term of Assent.…”
Section: Methodsmentioning
confidence: 99%
“…In summary, we replaced the questionnaire used for assessing depressive symptoms. We used the CES‐D questionnaire instead of the Beck questionnaire before enrollment of participants because the CES‐D was already validated for use in the Portuguese language 12 . Moreover, depressive symptoms were listed primary outcome in the revised version correcting a previous mistake that listed this variable as a secondary outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Quality-of-life measures are multidimensional and may emphasize physical/psychological condition, relationship quality, or perceptions about dignity, performance or autonomy (Ravens-Sieberer et al 2007). Social anxiety involves a fear of being embarrassed or humiliated in social interaction or in performance situations (Carvalho et al 2015). It tends to be particularly prevalent in adolescent peer relationships; its persistence and degree of impairment may lead to a psychological disorder also known as a social anxiety disorder (American Psychological Association 2013).…”
Section: Subjective Well-being: Definition and Indicatorsmentioning
confidence: 99%
“…The SAS-A was used as a whole measure of social anxiety in peer relationships, with an adequate internal consistency (α=.90), similar to the values of studies using the original English version (α=.91) (LaGreca and Lopez 1998) or the Portuguese version (α=.91)(Pechorro et al 2014). Depression.Depression was measured using the Portuguese version(Carvalho et al 2015) of the Center for Epidemiological Studies Depression Scale for Children (CES-DC)(Weismann, Orvaschel, & Padian, 1980). This questionnaire assesses depression in children and adolescents aged from 6 to 17 years old and encompasses 20 items (sample item: I felt low and unhappy) four of them reversed (sample item: I felt happy), covering emotional, cognitive and behavioral depressive dimensions.…”
mentioning
confidence: 99%